2020
DOI: 10.1101/2020.01.08.887828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Gene-Rich Genome of the ScallopPecten maximus

Abstract: AbstractBackgroundThe King Scallop, Pecten maximus, is distributed in shallow waters along the Atlantic coast of Europe. It forms the basis of a valuable commercial fishery and its ubiquity means that it plays a key role in coastal ecosystems and food webs. Like other filter feeding bivalves it can accumulate potent phytotoxins, to which it has evolved some immunity. The molecular origins of this immunity are of inte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 66 publications
(66 reference statements)
1
17
0
Order By: Relevance
“…This genome shared some typical features of other bivalves, such as a low GC content (32%) and a widespread presence of repeats (43% of the assembly), but it was particularly rich in both protein-coding (60,338) and non-coding (75,973) genes. While these figures largely exceed those observed in most sequenced bivalve species [12,14], they closely matched the numbers recently reported in the king scallop [17] and in the zebra mussel [41] (Additional file 1: Data Note 3). The reconstruction of the evolutionary relationships among M. galloprovincialis and 15 selected lophotrochozoan species [42][43][44][45], followed by an analysis of gene family trees [46], revealed that this large gene repertoire is the result of multiple lineage-specific duplication events that took place after the split between Mytilus and the rest of Mytilida (Fig.…”
Section: An Overview Of the Mussel Reference Genomesupporting
confidence: 84%
See 1 more Smart Citation
“…This genome shared some typical features of other bivalves, such as a low GC content (32%) and a widespread presence of repeats (43% of the assembly), but it was particularly rich in both protein-coding (60,338) and non-coding (75,973) genes. While these figures largely exceed those observed in most sequenced bivalve species [12,14], they closely matched the numbers recently reported in the king scallop [17] and in the zebra mussel [41] (Additional file 1: Data Note 3). The reconstruction of the evolutionary relationships among M. galloprovincialis and 15 selected lophotrochozoan species [42][43][44][45], followed by an analysis of gene family trees [46], revealed that this large gene repertoire is the result of multiple lineage-specific duplication events that took place after the split between Mytilus and the rest of Mytilida (Fig.…”
Section: An Overview Of the Mussel Reference Genomesupporting
confidence: 84%
“…Although M. galloprovincialis displays a morphologically conserved karyotype compared with other mussels and has not undergone known whole-genome duplication or allopolyploidization events [11], it shares with other bivalves a relatively large and complex genome, characterized by high heterozygosity and numerous mobile elements [12][13][14][15][16][17]. These factors posed a serious challenge to previous assembly efforts, which resulted in extremely fragmented genome sequences for this species [18,19] which, unlike the congeneric Mytilus coruscus [20] and a few other mussel species [15], still lacks a highly contiguous reference genome assembly.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of transcriptome and proteome analysis has been used to identify these proteins (e.g., Miyamoto et al 2013;Arivalagan et al 2017;Zhao et al 2018;Setiamarga et al 2020), with some data validated at the genomic level because of the availability of draft genomes (Mann et al 2012;Zhang et al 2012;Takeuchi et al 2016;Kenny et al 2020). Many of these proteins are present in trace amounts inside the shell and are therefore referred to as SMPs.…”
Section: An Overview Of Conchiferan Shell Matrix Proteinsmentioning
confidence: 99%
“…This gene codes for the enzyme pyrroline-5-carboxylate reductase 2 that catalyzes the conversion of pyrroline-5-carboxylate to proline, and proline has a protective effect against oxidative stress [ 65 ]. Kenny et al [ 66 ] suggested that mutations in the sodium channel gene, Neuron Navigator 1 ( Nav1 ), could protect against the effects of domoic acid in P. maximus . We have not found transcripts of the Nav1 gene in the digestive gland of P. maximus , therefore the sodium channel is likely expressed in nervous tissue but not in the digestive gland.…”
Section: Discussionmentioning
confidence: 99%
“…OmicsBox—Version 1.4.11.) [ 83 , 84 ], using local Blastx 2.10.0+ [ 88 ], (E-value threshold of 10 −3 ) against a database of Pecten maximus [ 66 ], Mizuhopecten yessoensis [ 89 ], Crassostrea gigas [ 70 ] and SwissProt proteins obtained from NCBI and UNIPROT:…”
Section: Methodsmentioning
confidence: 99%